(3TQM CMcGe bGfhf GdYed (B/s - (3TfH, eMeO dHjH,s (3Jhaj (B2016s; (3HfOb, hGFd CfhQs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2010)
(3jJNjd GdbGQF GdcQje aj gPG GdcJGH MLe GdegeI GdJj TQaJ HgG? heNGWQgG? hUYGHgG? hbO cGf Yedj aj JfbjM GdcJGH cGdJGdj, QGYjJ GdGMJaGX HJQbje GdHfhO ceG cGfJ MQUJ Ydi GdJejjR Hjf CUd GdcJGH hHjf GdEVGaGJ CeG Ydi GdUYjO GdJTQjYj beJ HJfbjM GdcJGH hakbG dCMcGe bGfhf GdYed GdLOjO Qbe (B12 (3dSfI (B2003 (3hYdi GdUYjO Gdabgj beJ HGdQLhY Edi cGaI eG cJH aj Xd bGfhf GdYed ShGA aj GdeDdaGJ GdYGeI Ch GdeJNUUI hCNjQG Ydi GdUYjO GdbVGFj hJJHYJ cGaI CMcGe eMceI GdfbV HTCf bGfhf GdYed MJi YGe (B2009.s
Keywords: (3GdYeds -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3YbhO GdYeds -- (3eUQs